Simulation-Based learning: Is it time for a paradigm shift in training postgraduates for crisis resource management? prospective interventional study - Soumya Umesh; Thenmozhi Nagarajan; Lakshmi Trikkur Anantharaman; Mary Joseph (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: Crisis resource management (CRM) skills are nontechnical skills that are often neglected during the training of residents in the management of clinical emergencies. This study was conducted to assess the utility of high-fidelity simulation to enhance the learning of CRM among internal medicine postgraduates (PGs). Materials and Methods: After obtaining IEC approval, a total of ten (five 1st year and five 3rd year) internal medicine PG students were included by convenience sampling. Each student participated in four simulated emergencies in the simulation laboratory of a tertiary care hospital, one before and three after CRM training. They participated in groups of 3–5 at intervals of 15–30 days. All the scenarios were video graphed and viewed by the investigators and each student was assessed in each session for CRM using Ottawa global rating score (GRS). The outcome variable was an overall score (OS-ordinal from 1to 7). After the last session, a questionnaire was administered to assess the perceptions of the participants about the course. After 1 year, the participants self-assessed their CRM in a real emergency using GRS and also identified barriers for the application of CRM in real life. The statistical tests used were paired t-test, Student's t-test, and repeated measures ANOVA. Results: The mean OS at baseline was 3.9 ± 1.5 and after training, it improved to 4.6 ± 1.26 (P = 0.024). In the three posttraining sessions, the OS did not decline and this indicated good retention of CRM (P = 0.056). PGs had a consistently favorable opinion of this course. The self-assessed OS in a real emergency was 5.7 ± 0.82. The barriers to CRM application in real emergencies were lack of practice and lack of team training. Conclusions: High fidelity simulation is an effective and acceptable method of teaching CRM to internal medicine PGs and should be incorporated into the PG curriculum.